Identification of novel APOB mutations by targeted next-generation sequencing for the molecular diagnosis of familial hypobetalipoproteinemia. (July 2016) - Rimbert, Antoine; Pichelin, Matthieu; Lecointe, Simon; Marrec, Marie; Le Scouarnec, Solena; Barrak, Elias; Croyal, Mikael; Krempf, Michel; Le Marec, Hervé; Redon, Richard; Schott, Jean-Jacques; Magré, Jocelyne; et al.
Abstract: Background and aims: Familial hypobetalipoproteinemia (FHBL) is a co-dominant disorder characterized by decreased plasma levels of LDL-cholesterol and apolipoprotein B (ApoB). Currently, genetic diagnosis in FHBL relies largely on Sanger sequencing to identify APOB and PCSK9 gene mutations and on western blotting to detect truncated ApoB species. Methods: Here, we applied targeted enrichment and next-generation sequencing (NGS) on a panel of three FHBL genes and two abetalipoproteinemia genes ( APOB, PCSK9, ANGPTL3, MTTP and SAR1B ). Results: In this study, we identified five likely pathogenic heterozygous rare variants. These include four novel nonsense mutations in APOB (p.Gln845*, p.Gln2571*, p.Cys2933* and p.Ser3718*) and a rare variant in PCSK9 (Minor Allele Frequency <0.1%). The affected family members tested were shown to be carriers, suggesting co-segregation with low LDL-C. Conclusions: Our study further demonstrates that NGS is a reliable and practical approach for the molecular screening of FHBL-causative genes that may provide a mean for deciphering the genetic basis in FHBL.